Real Games: What's Legitimate and What's Not in Contemporary Videogames - Consalvo (MIT Press, 2019)
Monograph
fulltext
Keywords: Computing and Processing; Components, Circuits, Devices and Systems; General Topics for Engineers; Power, Energy and Industry Applications